2022
DOI: 10.1159/000527155
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Mortality and Functional Outcome in Pregnancy and Puerperium-Related Cerebral Venous Thrombosis

Abstract: <b><i>Introduction:</i></b> Cerebral venous thrombosis (CVT) associated with pregnancy and puerperium has long been recognized, with poor information in terms of functional outcomes. Our objective was to analyze risk factors, clinical, imaging, and laboratory variables to predict functional outcome and death in this population. <b><i>Methods:</i></b> CVT registries from three referral centers from Pakistan, Turkey, and Mexico, recruiting prospective cases, were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 30 publications
(43 reference statements)
2
7
0
Order By: Relevance
“…Approximately 80% of pregnancy-related CVT cases occur after delivery. 12 10 Overall, studies published since the prior scientific statement 1 have found that the prognosis for women with pregnancy-related CVT is better than or the same as that for patients with CVT in general. 71 VKAs, including warfarin, are associated with fetal embryopathy and bleeding in the fetus and neonate and thus are contraindicated in pregnancy.…”
Section: Cvt During Pregnancy and Puerperiummentioning
confidence: 98%
See 4 more Smart Citations
“…Approximately 80% of pregnancy-related CVT cases occur after delivery. 12 10 Overall, studies published since the prior scientific statement 1 have found that the prognosis for women with pregnancy-related CVT is better than or the same as that for patients with CVT in general. 71 VKAs, including warfarin, are associated with fetal embryopathy and bleeding in the fetus and neonate and thus are contraindicated in pregnancy.…”
Section: Cvt During Pregnancy and Puerperiummentioning
confidence: 98%
“…Women with a history of VTE appear to have an increased risk of thrombotic events (ie, deep venous thrombosis, pulmonary embolism) in future pregnancies. 64 A systematic review comprising 17 studies and 393 pregnancies found a recurrence rate of 8 per 1000 pregnancies (95% CI, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The rate of noncerebral VTEs was 22 per 1000 pregnancies (95% CI, 11-43).…”
Section: Future Pregnancies and Recurrencementioning
confidence: 99%
See 3 more Smart Citations